2007
DOI: 10.1080/02705060.2007.9664171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epiphytic Algae on Photosynthetic Function ofPotamogeton crispus

Abstract: The effect of blooming epiphytic algae on the leaf traits and photosynthetic hnction of the submersed macrophyte Potamogeton crispus was investigated under different epiphytic conditions and nutrition levels. Epiphytic algae growth was promoted at a rate of 0.16 chl a pg.cm".d-' on leaf surface area under eutrophic conditions (N: 1 mg.L-'; P: 0.1 mg-L-') and at a rate of 0.004 chl a pg-~m-~.d-' under mesotrophic conditions (N: 0.1 mgL-'; P: 0.01 mg.~-'). In the presence of the algae eaters Macrobrachiurn nippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The chl-a/chl-b ratio reflecting the light utilization efficiency of photosynthesis in leaves of plants suggested that epiphytic algae aggravated the adverse influence on light utilization efficiency of V. natans at 2.5-5 mg/L nitrate-N in the water column, when epiphytic algal biomass was reaching a high level. This result was consistent with the demonstration that an epiphytic algal boom resulted in the decline of chl-a density in the leaves of plants [33,34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The chl-a/chl-b ratio reflecting the light utilization efficiency of photosynthesis in leaves of plants suggested that epiphytic algae aggravated the adverse influence on light utilization efficiency of V. natans at 2.5-5 mg/L nitrate-N in the water column, when epiphytic algal biomass was reaching a high level. This result was consistent with the demonstration that an epiphytic algal boom resulted in the decline of chl-a density in the leaves of plants [33,34].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the overgrowth of epiphytic algae rather than planktonic algae may be the most important factor leading to the loss of submerged macrophytes [23,31]. In fact, the results of many previous studies have suggested that the presence of dense epiphytic algae populations inhibits the growth of submerged macrophytes [32][33][34], mainly by reducing light and nutrient availability for the plants [29,35], which may further lead to the loss of submerged macrophytes. As a consequence, the clear-water state in shallow lakes is transformed into a turbid-water state with a high density of phytoplankton [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Epiphytic algae covering the surface of plants could serve as a food source for higher levels of the aquatic food chain and affect growth and development of submerged plants in water ecosystem (Goldsborough et al 2005;Chen et al 2007). In eutrophic water bodies, especially those containing high level of planktonic algae, epiphytic algae greatly reduced light and nutrient availability for submerged plants, which led to adverse effects on the growth of submerged plants.…”
Section: Resultsmentioning
confidence: 99%
“…With specific regard to IBMR, this method has been claimed to be a better indicator of pH and/or carbon availability both as HCO 3 and pCO 2 , rather than an indicator of soluble reactive phosphorus and/or NH 4 + (Demars and Tré moliè res, 2009;Demars et al, 2012). Referring to algae, the reciprocal dominance relationships between tracheophytes and algae are complex and not limited to variations in the trophic status and/or N/P ratio (Doyle and Smart, 1998;Walstad, 1999;Chen et al, 2007). The inverse correlation between algae and tracheophytes observed during present survey, in particular in the fourth and fifth tract, has been already described in springs and represents a form of competition (Hauxwell et al, 2004;Frazer et al, 2006a,b;Jacoby et al, 2007).…”
Section: Discussionmentioning
confidence: 97%